Unveiling consumer perspectives on district heating: A Q methodology study - Radtke, Uwe (International Journal of Innovative Research and Scientific Studies, 2024)
This study uses the Q methodology to investigate consumer perspectives on district heating, combining qualitative and quantitative methods across five research phases: foundation development, statement compilation (the Q-set), participant selection (the P-set), Q sorting and data analysis. The foundation was built using diverse sources yielding 39 statements. Experts from various disciplines were involved in the selection of statements using a two-round Delphi-like method to ensure objectivity. Subsequent steps included recruiting participants with varied perspectives, conducting Q sorting and analyzing data to reveal thought patterns. This research aims to shed light on consumer viewpoints regarding district heating, sustainability and general attitudes, assisting policymakers in promoting environmentally friendly energy practices. This research employs the Q methodology to collect and analyze subjective viewpoints concerning district heating, enhancing our understanding of consumer perspectives and their implications for sustainable energy systems. The results indicate a positive attitude towards district heating with strong support for further research and investment. Additionally, it aims to clarify the paper's results by highlighting the diverse consumer attitudes towards pricing mechanisms. The findings suggest transparent pricing mechanisms influenced by user behavior are more likely to gain acceptance. Four groups were found by using K-means clustering to analyse the data. These clusters showed preferences for longer, steady operating hours with low demand followed by shorter hours with low demand and resistance towards low operating hours with high demand. Future research could explore specific consumer profiles, private data or leverage waste heat from sources.